Empire, Islam, and politics of difference - Kuehn, Thomas. (Leiden ; Boston)
xviii, 292 sayfa
Keywords: “Historians of the Middle East in the long nineteenth century have often considered empire-building the preserve of European powers. This book revises that picture by exploring how the Ottomans re-conquered and ruled large parts of present-day Yemen between 1849 and the end of World War I, after more than two centuries of independence under local dynasties. Drawing on a wide range of sources and on recent scholarship on empire and colonialism, Empire, Islam, and Politics of Difference shows how the concepts and practices of Ottoman imperial rule were shaped through the encounters between Ottoman officials, their European rivals, and local communities. The result is a fresh look at the nature of governance in the late Ottoman Empire more generally.” --